Sexuality: Sexual Attitude and Behaviour of Adolescents in Tertiary Institutions in Nigeria. - Tenibiaje, Dele Joseph (Advances in Social Sciences Research Journal, 2014)
This study investigated sexuality in adolescents and determined sexual activities, sexual behaviour and effectiveness of contraceptive usage most effective among university adolescents. The study employed the descriptive design of the survey type. The sample consisted of 400 university students selected from different faculties from two different universities in Ekiti State. Simple random and stratified sampling techniques were used to select the sample. A self-designed instrument was used to collect data from respondents and the data were subjected to descriptive statistics. The instrument was validated by using face and content validities. The reliability of the instrument was established through test-retest procedure. Five research questions were raised to guide the direction of the study. It appears as if sexuality was influenced by culture, religions and peers which shaped the ideas, attitude and behaviour of university students. It appears as if sexual activities were prevalent, practised and thrived among the adolescents. Since sexuality is a natural, innate and normal phenomenon among adolescents, then there should be a way out. It is recommended that sexuality education should be introduced to adolescents and a sexuality education programme should be put in place to curb the prevalence among them.